Effects of air gap on membrane substrate properties and membrane performance for biomass processing - Elfira, Anuar; Syed Mohd Saufi, Tuan Chik; Hafizuddin, Wan Yussof (Springer, 2019)
In this study, a correlation between the membrane substrate properties and the final performance of hollow fiber thin film composite (TFC) membrane for xylose/glucose concentration and acetic acid removal was studied. Polysulfone (PSf) hollow fiber membrane substrate was fabricated using 20 wt% PSf, 2 wt% polyvinylpyrrolidone and 78 wt% dimethylformamide via dry-wet spinning process. The air gap distance was manipulated from 6 cm to 15 cm during spinning in order to produce different substrate membrane properties. The molecular weight cut-off (MWCO) and porosity of the membrane substrate increased as the air gap distance increased. Membrane substrate that was spun at 6 cm air gap showed a rapid phase inversion without much chain relaxation, thus producing the smallest MWCO (8 kDa) and an average pore diameter (4.46 nm). The TFC membrane produced using this membrane substrate showed the best performance in terms of solute rejection and separation factor. The rejection for xylose, glucose and acetic acid were 91.66 ± 0.09%, 67.28 ± 13.97%, and 13.08 ± 3.00%, respectively. This results in ideal separation factor of 3.20 ± 1.27 for acetic acid/glucose and 10.42 ± 0.25 for acetic acid/xylose.